The Influence of Islamic Corporate Governance and Islamic Corporate Social Responsibility on Financial Performance in Indonesian Sharia Commercial Bank - Annissa, Ella; Nurlaila, Nurlaila; Samri Juliati Nasution, Yenni (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The development of Sharia banks is marked by the growth of sharia banks and the number of sharia bank offices from year to year. This growth in the number of banks and assets should also be accompanied by an increase in the performance of Islamic banks themselves, which can be seen from the large financial ratios of these Islamic banks. This research aims to examine the influence of Islamic Corporate Governance and Islamic Corporate Social Responsibility simultaneously on the performance of sharia banking. This type of research is quantitative research with a sample size of 42 financial report data from Sharia Commercial Banks from 2018-2020. The results obtained in this research are that ICG (Islamic Corporate Governance) has a positive and significant effect on ROA (Return on Assets) with t count 4.775678 > t table 1.68488 and ICSR (Islamic Corporate Social Responsibility) has a positive and significant effect on ROA (Return on Assets) t count 6.295548 > t table 1.68488. Then simultaneously ICG (Islamic Corporate Governance) and ICSR (Islamic Corporate Social Responsibility) on ROA (Return on Assets) with F-count 375.3721 > F-table 3.245 with an r-squared value of 0.947 or 94.7% explained by the variables ICG and ICSR and the remaining 5.3% are influenced by other variables outside this study.